Criminal Sanctions and State Loss: A Review of Corruption Sentencing Under the New National Penal Code - Jessyca H. Picauly; Adolof Seleky; Imanuel J. Lawalatta (Legtimacy: Journal of Law and Islamic Law, 2026)
This research examines the transformation of corruption sentencing under Indonesia’s Law Number 1 of 2023 (National Penal Code) compared to Law Number 31 of 1999. Utilizing a normative-juridical approach, the study analyzes Article 603 of the new code, which significantly reduces the minimum imprisonment from four to two years. Critics argue this undermines the "extraordinary crime" status of corruption. However, this analysis reveals a legislative shift toward proportional justice and economic efficiency. The reduction addresses practical imbalances where judicial costs for small-scale corruption exceed actual state losses. Furthermore, the new code integrates restorative values and asset recovery over purely retributive punishment. Findings indicate that while minimum sanctions decreased, maximum fines increased to target large-scale perpetrators. Ultimately, effectiveness relies on judicial discretion and asset tracing to ensure legal certainty and protection of state finances within Indonesia’s evolving national legal system ensuring justice for all citizens while maintaining strong anti-corruption institutional integrity.